- PENGARUH INTERAKSI SOSIAL TEMAN SEBAYA TERHADAP KECERDASAN EMOSIONAL ANAK USIA 5-6 TAHUN DI TK ISLAM IBNU KHALDUN BENGKONG KOTA BATAM - Nurhayati, Nurhayati; Fatma, Novita Putri; Maulani, Denisa Putri (Bunayya, 2026)
This study aims to analyze the relationship between peer social interaction and the emotional intelligence of children aged 5–6 years. The research employed a quantitative approach with a cross-sectional correlational design. The study involved 72 children from Ibnu Khaldun Islamic Kindergarten in Bengkong, with data collected through Likert-scale questionnaires completed by parents. Data analysis was carried out using Pearson’s product-moment correlation after the assumptions of normality and linearity were met. The findings reveal a significant relationship between peer social interaction and children’s emotional intelligence, with a correlation coefficient of r = 0.51 and a significance level of p < 0.001. These results indicate that the quality of social interaction is meaningfully associated with the development of emotional intelligence in early childhood. The coefficient of determination (R² = 0.26) suggests that peer social interaction contributes to the variation in children’s emotional intelligence, although other factors beyond the scope of this study also play a role. Practically, the findings emphasize the importance of providing learning environments that support positive social interactions—such as cooperative play activities and structured social habituation—as part of efforts to strengthen the social-emotional development of young children